Fostering inclusive learning in primary science education emphasizing activity and cooperation. Präsentation auf der 16th Biennial EARLI Conference for Research on Learning and Instruction - Blumberg, Eva; Hellmich, Frank; Fromme, Theresa

Soziales Kapital und Nachbarschaft - Landhäußer, Sandra (Soziale Nachbarschaften: Geschichte, Grundlagen, Perspektiven)
Nachbarschaft erfährt aktuell in nationalen wie regionalen Programmen, in städtischen Leitpapieren und kommunalen Initiativen eine Hochkonjunktur. Ihr wird für die Erlangung von Gemeinschaft(en) im Lokalen eine besondere Rolle zugesprochen und sie kann – so die dominierende Vorstellung der Programme und Initiativen – durch professionelle Gestaltung angeregt bzw. initiiert werden. Das Buch macht sich auf die Spurensuche nach Nachbarschaftskonzepten und -thematisierungen, ordnet diese in aktuelle theoretische Vergemeinschaftungsdiskurse ein und eröffnet mit dem Konzept der Sozialen Nachbarschaften Perspektiven für Nachbarschaftspolitiken und die professionelle Arbeit mit bzw. in Nachbarschaften.
Keywords: Soziale Nachbarschaften; Nachbarschaftsthematisierungen

Zur Neuthematisierung von Familie als Erziehungs- und Bildungsort : Konsequenzen und Herausforderungen für Eltern- und Familienbildung - Landhäußer, Sandra; Faas, Stefan (Neue Aufmerksamkeiten für Familie)

An asymptotic LMPI test for cyclostationarity detection with application to Cognitive Radio (invited paper) - Ramírez, D.; Schreier, P. J.; Vía, J.; Santamaría, I.; Scharf, L. L. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
We propose a new detector of primary users in cognitive radio networks. The main novelty of the proposed detector in comparison to most known detectors is that it is based on sound statistical principles for detecting cyclostationary signals. In particular, the proposed detector is (asymptotically) the locally most powerful invariant test, i.e. the best invariant detector for low signal-to-noise ratios. The derivation is based on two main ideas: the relationship between a scalar-valued cyclostationary signal and a vector-valued wide-sense stationary signal, and Wijsman’s theorem. Moreover, using the spectral representation for the cyclostationary time series, the detector has an insightful interpretation, and implementation, as the broadband coherence between frequencies that are separated by multiples of the cycle frequency. Finally, simulations confirm that the proposed detector performs better than previous approaches.

An Experimental Evaluation of Broadband Spatial IA for uncoordinated MIMO-OFDM Systems - Fanjul, Jacobo; Lameiro, Christian; Santamaría, Ignacio; García-Naya, Jose A.; Castedo, Luis (Proc. IEEE Int. Conf. Digital Signal Process.)
In this paper we present an experimental study on the performance of spatial Interference Alignment (IA) in broadband indoor wireless local area network scenarios that use Orthogonal Frequency Division Multiplexing (OFDM) according to the IEEE 802.11a physical-layer specifications. Experiments have been carried out using a wireless network testbed made up of six nodes equipped with Multiple-Input Multiple-Output (MIMO) radio interfaces. This setup allows the implementation of a 3-user MIMO interference channel. We have implemented different IA decoding schemes that operate either before or after the Fast Fourier Transform block. IA has been experimentally evaluated comparing both approaches to analyze its performance in synchronous and asynchronous transmissions. Our results indicate that spatial IA performs satisfactorily in practical broadband indoor scenarios in which wireless channels often exhibit relatively large coherence times.

Ranging with high accuracy and without ambiguities - Theiler, Sebastian; Stein, Manuel; Nossek, Josef A. (Proc.\ IEEE Work. Pos.\ Nav. & Com.)

Benefits of Improper Signaling for Underlay Cognitive Radio - Lameiro, Christian; Santamaría, Ignacio; Schreier, Peter J. (IEEE Wireless Comm. Lett.)

Analysis of maximally improper signalling schemes for underlay cognitive radio - Lameiro, Christian; Santamaría, Ignacio; Schreier, Peter J. (Proc.\ IEEE Int.\ Conf.\ Comm.)
In this paper, the impact of improper Gaussian signaling is studied for an underlay cognitive radio (CR) scenario comprised of a primary user (PU), which has a rate constraint, and a secondary user (SU), both single-antenna. We first derive expressions for the achievable rate of the SU when it transmits proper and maximally improper Gaussian signals (assuming that the SU is solely limited by the CR constraint). These expressions depend on the channel gains to and from the SU through a single variable. Thereby, we observe that improper signaling is beneficial whenever the SU rate is below a threshold, which depends on the signal-to-noise ratio (SNR) and rate requirement of the PU. Furthermore, we provide bounds on the achievable gain that also depend only on the PU parameters. Then, the achievable rate is studied from a statistical viewpoint by deriving its cumulative distribution function considering a constant received SNR at the PU. In addition, we specialize this expression for the Z interference channel, for which the expected achievable rate is also derived. Numerical examples illustrate our claims and show that the SU may significantly benefit from using improper signaling.

Overdemodulation for high-performance receivers with low-resolution ADC - Stein, Manuel; Sebastian, Theiler; Nossek, Josef A. (IEEE Wireless Comm. Lett.)

Determining the number of correlated signals between two data sets using PCA-CCA when sample support is extremely small - Song, Y.; Schreier, P. J.; Roseveare, N. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)